Oncological Safety of Breast Conserving Surgery in Breast Cancer - Guzijan, Aleksandar; Gajanin, Radoslav; Ćulum, Jovan; Gojković, Zdenka; Preradović, Ljubiša; Roganović, Dragana (Scripta Medica, 2022)
Background/Aim: Breast-conserving surgery is a type of surgery used as a treatment option for breast cancer. It was introduced at the end of the 20th century following and in accordance with relevant clinical studies. With heightened public awareness of breast cancer and the introduction of new diagnostic procedures, despite the proven oncological safety of this type of surgery, a growing number of women choose to undergo total mastectomy. The aim of this study was to confirm the oncological safety of breast-conserving surgery performed on breast cancer patients at the University Clinical Centre of the Republic of Srpska.Methods: This study analysed 305 female patients with I and II stage of breast cancer, operated on between March 2009 and December 2013. One group of patients underwent breast-conserving surgery (BCS), followed by adjuvant radiation therapy and the other total mastectomy (MX). The patients were followed up for 5 years after the surgery. Analysed herein were the local-regional recurrence, distant metastases, disease-free survival and overall survival rates. Results: After a five-year follow-up, the local-regional recurrence rate for patients in the BCS group was 4.3 %, while for the MX group it was 4.2 %. The overall survival rate of patients in the BCS group was 90.9 %, as opposed to 89.1 % for MX patients.Conclusion: After a five-year follow-up, no statistically significant difference was observed between the two groups of patients regarding the local-regional recurrence (p = 0.967) and overall survival rates (p = 0.610). Breast-conserving surgery is an oncologically safe surgical treatment for breast cancer.
Keywords: Breast cancer; Mastectomy; Breast-conserving surgery; Breast centre; Radiation therapy